Assessment of the technical condition of historic mansions – a proposal for standardization of documentation - Kendzierawska, Weronika; Trochonowicz, Maciej (Teka Komisji Architektury, Urbanistyki i Studiów Krajobrazowych, 2022)
In contrast to palace assumptions, which in most cases in the Lublin region are in good technical condition, a significant number of manor houses are in satisfactory condition. Manor buildings, due to their much lower historical and monumental value, clearly inferior quality of materials and complicated ownership status, have largely fallen and continue to fall into disrepair. The analyses carried out have shown that in the relatively small area of Lublin Province there are a number of objects that require extensive design and renovation work. All these works must be preceded by a detailed analysis of the technical condition. Such documentation should include: up-to-date inventories, technical descriptions, technical condition assessments, basic in situ and laboratory tests. This article is an attempt to standardize the documentation The proposal is presented on the example of a 20th-century manor house in the village of Zamieście, for which drawing and photographic documentation was prepared, moisture and mycological tests were performed, and a detailed technical condition assessment was made.